Integrasi Deep Learning dan Pendidikan Karakter Berbasis Nilai dalam Upaya Penguatan Kompetensi Guru SMP Negeri 20 Kota Malang - Yayuk, Erna; Iswatiningsih, Daroe (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2026)
Strengthening teacher competence is a strategic effort to improve the quality of learning at the junior high school level. Current educational challenges require teachers not only to master subject content and teaching methods but also to design and implement deep learning approaches integrated with value-based character education. This community service program aimed to enhance the conceptual understanding and pedagogical skills of teachers at SMP Negeri 20 Malang in integrating deep learning with character value reinforcement in the learning process. The program was implemented through workshops, mentoring, limited classroom implementation, and continuous evaluation. A total of 30 teachers from various subject areas participated in the activity. The results indicate a significant improvement in teachers’ understanding of deep learning, reflected in a shift from content-oriented instruction toward meaningful and reflective learning. In addition, teachers demonstrated improved competence in designing learning tools that integrate cognitive and affective dimensions as well as character values, supported by the use of authentic assessment. This program contributes to the development of contextual, sustainable, and character-oriented learning practices that support students’ holistic development.